Development of Bird Learning Application by Using Augmented Reality - Jailani, Athira Balqis; Murli, Norhanifah (Applied Information Technology And Computer Science, 2026)
Learning about pet birds is essential for ensuring their health, happiness, and longevity. However, many bird owners lack access to clear, interactive resources that provide accurate and practical guidance. This study aims to address the lack of information among bird owners using a mobile application with Augmented Reality (AR) technology. The developed application provides users with helpful and easy-to-understand guidance. Birdie: Pet Focus uses marker-based AR technology to enhance interactivity and is designed for users aged 16 to 45. The AR features allow users to view five types of 3D bird models within the app: Canary, Parrot, Lovebird, Zebra Finch, and Dove. Through the application, users can access detailed information on bird species, bird health, and bird care tips. This application is developed in English and will be available on the Android platform. The development of Birdie: Pet Focus is based on the Multimedia Mobile Content Development (MMCD) methodology. This application consists of five modules: the species information module, the disease module, the diet and care module, the activity module, and the AR module. It is intended for bird owners, pet shops, or anyone interested in learning about pet birds. Based on the System Usability Scale (SUS) results, the application scored above average, indicating that users found it usable, interactive, and well-suited for its intended purpose.